A Model Analysis of the Effect of Self-Efficacy, Authoritative Parenting, and Peer Social Support on Academic Stress in Full-Day Senior High School Students - izzati, indah dwi cahya; Tentama, Fatwa; Suyono, Hadi (ANFUSINA: Journal of Psychology, 2023)
This study investigated the influence of self-efficacy, authoritative parenting, and peer social support on academic stress in full-day senior high school students. The population of this study were all twelfth-grade students from Senior High School X in Lampung, with a total of 330 students. This study involved 140 twelfth-grade students as the participants were selected using a cluster random sampling technique. This study employed an academic stress scale, self-efficacy scale, authoritative parenting scale, and peer social support scale. The data was analyzed by evaluating the outer and inner models. The study employed the Structural Equation Model (SEM) for data analysis using the Smart Partial Least Square 3.3.0 application. The findings of this study include the development of a model of the influence of self-efficacy, authoritative parenting, and peer social support on academic stress that is consistent with empirical data, the absence of an effect of self-efficacy on academic stress, a very significant negative influence between authoritative parenting and academic stress, and a very significant negative influence between peer social support and academic stress. The theoretical model developed in this study is a fit model, which can be used as a valid model reference when addressing academic stress.